Advanced optimal by PSO-PI for DC motor - Salam Waley Jeaeb; Abbas Zghair Salman; Qusay A. Jawad; Haider Shareef (Institute of Advanced Engineering and Science, 2019)
Interest in the drive system which used in many applications is increasing day by day. So, many researchers have focused on the analyses, design and control of these systems. In this study, Optimal for Dc motor in drive system control strategy has been proposed for PSO-PI and fuzzy logic controller (FLC) based Dc motor in drive system. In order to test dynamic performance of PSO-PI based drive System, simulation study was carried out by MATLAB/Simulink. The results obtained from the PSO-PI based drive system are not only superior in the rise time, settling time and overshoot but can prevent from voltage and has improved power quality.